Czechoslovak Civilising Mission: Assimilation Practices for ‘Gipsy’ Children in 1918–1942 - Baloun, Pavel (Dějiny – teorie – kritika, 2018)
This study offers a qualitative analysis of two interrelated practices implemented in interwar Czechoslovakia with respect to ‘gipsy children’. First of all, it deals with the so-called ‘gipsy schools’, which were in practice separate auxiliary classes for ‘gipsy children’ established in Slovakia and Transcarpathian Ruthenia in 1927–1938. In the following, the author outlines a practice of taking children from families which were based on Czechoslovak law on ‘vagrant gipsies’, adopted in 1927, identified by authorities as ‘vagrant gipsies’. Both of these separate and largely regionally applied approaches are set within a wider context of implementation of state administration in the areas in question (eastern Slovakia and Transcarpathian Ruthenia on the one hand and Bohemia on the other hand) and within a context of contemporary expert discussions about a ‘re-education of gipsy children’. The author argues that these were two distinct approaches to assimilation of ‘gipsies’ into the Czechoslovak society, that is, to integration based on erasing and fully removing the alleged ‘gipsy’ differentness.